Projective Vector Fields on Semi-Riemannian Manifolds - Norah Alshehri; Mohammed Guediri (Mathematics, 2024)
This paper explores the properties of projective vector fields on semi-Riemannian manifolds. The main result establishes that if a projective vector field P on such a manifold is also a conformal vector field with potential function <semantics>ψ</semantics> and the vector field <semantics>ζ</semantics> dual to <semantics>dψ</semantics> does not change its causal character, then P is homothetic, or <semantics>ζ</semantics> is a light-like vector field. Additionally, it is shown that a complete Riemannian manifold admits a projective vector field that is also conformal and non-Killing if and only if it is locally Euclidean. The paper also presents other results related to the characterization of Killing and parallel vector fields using the Ricci curvature and the Hessian of the function given by the inner product of the vector field.